THE DEVELOPMENT OF SOCIAL SKILLS OF YOUNG PEOPLE LIVING IN COMMUNITY CARE HOMES - Raudeliunaite, Rita; Gudžinskienė, Vida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The purpose of the article is to reveal the need for the social skills of young people living in community care homes based on the experience of young people. Problematic study questions: What social skills, which are important to a person‘s independent living, do the adolescents lack?  How do opportunities to develop social skills change while living in the community care homes? Eight young people aged 17-18 years old from three community care homes, which are in different parts of Lithuania, participated in the study. The study revealed that young people lack communication skills: they have difficulty establishing and maintaining contact, communicating politely, being empathetic (careful, attentive and understanding to others), addressing emerging issues and conflicts constructively. The study found out that young people lack intrapersonal skills: self-control, responsibility, and self-confidence. Young people lack activity organisation skills: activity planning and activity realisation skills. The study reveals that, while living in community child care homes, opportunities to develop social skills change in a positive way. In everyday practical activities, more opportunities to solve problems and plan and organise various activities occur. By communicating and cooperating in the family environment, young people acquire more empathy, building rapport and maintaining it, polite communication and conflict resolution skills. A family atmosphere and close and positive mutual relationships, which are built in the community child care homes, contribute to the strengthening of self-confidence and trust in others.